Progression in Physical Frailty in Peritoneal Dialysis Patients - Gordon Chun-Kau Chan; Jack Kit-Chung Ng; Kai-Ming Chow; Vickie Wai-Ki Kwong; Wing-Fai Pang; Phyllis Mei-Shan Cheng; Man-Ching Law; Chi Bon Leung; Philip Kam-Tao Li; Cheuk-Chun Szeto (Karger Publishers, 2021)
Background: Physical frailty contributes to adverse clinical outcomes in peritoneal dialysis (PD) patients. Little has been reported about frailty transitions in this population. We aimed to describe the transitions of frailty in PD patients and identify factors that predicted changes in frailty state. Methods: In a prospective observational study, we recruited 267 PD patients. Frailty was assessed by a validated frailty score. Depression was graded by PHQ-9 score, and nutritional status was evaluated by serum albumin, Subjective Global Assessment (SGA), and comprehensive Malnutrition Inflammation Score (MIS). The primary outcome was the change in frailty score at follow-up compared to baseline. Results: At baseline, 194 (72.7%) patients were classified as frail. With time, their frailty scores significantly increased (p < 0.001), and 93 of the surviving subjects (78.2%) were classified as frail. There was a modest significant correlation between change in MIS (p < 0.001), change in SGA score (p < 0.001), and change in PHQ-9 score (p < 0.001) with change in frailty score. An increase in PHQ-9 score (p < 0.001) and MIS (p = 0.001), as well as longer duration of hospitalization (p = 0.001), was independently associated with a greater change in frailty score after adjustment for confounding factors. Frailty score was also improved in patients who were converted to hemodialysis (p = 0.048) and received renal transplantation (p = 0.005). Conclusion: Our findings suggested that frailty transitions were common in PD patients. Worsening in nutrition and depression, together with a longer duration of hospitalization, were associated with worsening in frailty.